Structural and optical properties of SbxSey thin films obtained by chemical molecular beam deposition method from Sb and Se precursors. (April 2023) - Razykov, T.M.; Bekmirzoev, J.; Bosio, A.; Ergashev, B.A.; Isakov, D.; Khurramov, R.; Kouchkarov, K.M.; Makhmudov, M.A.; Romeo, A.; Romeo, N.; Tivanov, M.S.; Utamuradova, Sh.B.; et al.
Highlights: Influence of Sb/Se ratio of Sb2 Se3 films were investigated. Sb2 Se3 films with different compositions fabricated by CMBD method from separate sources of Sb and Se. The Se content in the solid phase is directly proportional to the Se content in the vapour phase during the growth process. Sb2 Se3 thin films with micro-sized crystal grains exhibit ( hk 1) preferential orientation at the stoichiometric composition. Abstract: Sbx Sey thin-films were obtained by chemical-molecular beam deposition (CMBD) on soda-lime glass from Sb and Se precursors. By the precise control of the Sb/Se ratio, Sb2 Se3 thin films with stoichiometric composition were successfully obtained. The elemental and phase composition, as well as the crystal structure of Sbx Sey thin-films, were studied by energy-dispersive X-ray microanalysis, X-ray diffraction, Raman spectroscopy, scanning electron microscopy and atomic force microscopy. The optical bandgap of the films was determined from the absorption spectra acquired by a spectrophotometer. The physical properties of Sbx Sey thin films with different compositions were investigated.